Resolusi Konflik Pemanfaatan Sumberdaya Pesisir antara Nelayan dengan Penambang Timah Inkonvensional: Conflict Resolution in Coastal Resource Utilization among Fishermen and Unconventional Tin Miners - Endang Bidayani; Kurniawan Kurniawan (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
Coastal as an open-access resource has the potential to cause conflict with spatial use. This research aims to analyze the conflict in the utilization of coastal resources among fishermen and unconventional tin miners. This research used a survey research method with qualitative descriptive research, including income analysis, employment opportunities, education, and health. Respondents in this research were fishermen and unconventional tin miners in Bangka Tengah district, including Batu Belubang village - Pangkalan Baru sub-district, Kurau village - Koba sub-district, and Baskara Bhakti village - Namang sub-district. Data collection using methods through observation, interviews, and documentation. Conflicts are analyzed through a stakeholder analysis approach with an onion analysis approach. The results showed that there were four main issues triggering conflict: 1) environmental issues; 2) social issues; 3) law violation issues; 4) economic issues. Conflict resolution that is collaborative with a negotiation approach that combines elements of the user community (fishing groups and unconventional miners) and the government known as Co-Management which avoids the excessive dominant role of one party in the management of coastal and marine resources, including equitable division of territory between fishing and mining areas, with reference to coastal and marine spatial regulations in the Bangka Belitung Islands Province, Indonesia.